Correlation between family knowledge and preventive behaviors against pulmonary Tuberculosis transmission at regional hospital - Manurung, Togu Pandi Marihot; Manurung, Bintang Kasih; Manurung, Lastiurma (Asian Journal of Toxicology, Environmental, and Occupational Health, 2026)
Background: West Kalimantan Province ranks 15th in tuberculosis case notification rates and has the highest rate among the 34 provinces in Indonesia. One of the contributing factors to the incidence of tuberculosis is the poor behavior and attitudes of families. Therefore, family knowledge regarding the prevention of pulmonary tuberculosis transmission is important to be studied further. Methods: This study employed a quantitative research method using a cross-sectional approach. Data were collected through questionnaires. The sample consisted of the entire population included in the study, totaling 22 respondents. Data were analyzed using univariate and bivariate analysis techniques. Findings: The study showed that most respondents had good knowledge about pulmonary tuberculosis. Furthermore, respondents demonstrated good preventive behaviors against tuberculosis transmission, which were influenced by their adequate knowledge. Conclusion: This study concludes that there is a significant relationship between family knowledge and preventive behaviors toward pulmonary tuberculosis transmission in the Infectious Disease Ward of Regional General Hospital. Novelty/Originality of this article: This research focuses on the family context in disease prevention and health promotion. In addition, the study uses the most recent data relevant to current public health needs, providing updated evidence that supports the continuity of tuberculosis prevention research.